Intraspecific and temporal variability in the diet composition of female polar bears in a seasonal sea ice regime - Luana Sciullo; Gregory W. Thiemann; Nicholas J. Lunn; Steven H. Ferguson (Canadian Science Publishing, 2017)
Predator foraging behaviour is influenced by a suite of intrinsic and extrinsic factors, including energetic requirements, resource availability, and habitat conditions. Polar bears (Ursus maritimus) are specialized predators of marine mammals and are adapted to a seasonal sea ice regime in much of their range. We used quantitative fatty acid signature analysis to estimate the diet composition of 374 female polar bears from 2004 to 2014 in western Hudson Bay, Canada. Ringed seal (Pusa hispida) was the dominant prey species followed by bearded seal (Erignathus barbatus) and harbour seal (Phoca vitulina), with minimal consumption of beluga whale (Delphinapterus leucas), harp seal (Pagophilus groenlandica), and walrus (Odobenus rosmarus). Solitary adults and females supporting yearling cubs consumed more bearded seal than did subadults or females with cubs-of-the-year (COY). Subadults may be too small or inexperienced to capture bearded seals and females with COY may avoid offshore pack ice where densities of bearded seals, and potentially infanticidal adult male polar bears, may be highest. A relatively high dietary diversity in subadults and females supporting COY suggests less selective foraging and opportunistic scavenging. Overall, bears consumed more harbour seal and less ringed seal in congruent years, suggesting variable local prey availability. Date of sea ice breakup influenced the diet of subadults and family groups more so than solitary females, suggesting differential sensitivity to sea ice conditions. Interannual variability in diet may be a consequence of differing responses of polar bears and multiple prey species to sea ice conditions in Hudson Bay.